La costruzione della verità giudiziaria The Building of the Judicial Truth - Marcella Marmo (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2003)
Legal processes have often been at the core of the public debates. In the West, keeping in mind the political and social chaos between the 18th century and the contemporary world, it is possible to see how circles of opinion often were pervaded and tangled by tales carried out in the courtrooms. The reconstruction of the events as well as of the dynamics that, through these paths, entered into the costume and the society of the time requires the historian to a close analysis of sources as well as of procedures connected to the judicial activity. The essays published in this book aim at providing some elements of reflection about the judicial truth, considering it as a sort of "building" with its epistemological knots and different interpretations, crossing experiences deriving from sociological, historical-juridical, historical-political and politico-logical analysis.